Guide to business planning - Friend, Graham; Zehle, Stefan (London : Profile Books, 2009)
To get any new business idea off the ground or develop and better manage an existing business, you must have a plan$1 (Band if you need to raise finance to fund the business or get the approval of senior management, it must be a convincing plan. This comprehensive guide covers every aspect of preparing and using a business plan. It explains: tools for analysing the market, customers, competitors and the business environment techniques for examining and choosing between different strategic options how to use the business planning model that accompanies this book to prepare financial forecasts how to analyse and mitigate risk how to identify the business's financing needs and select the appropriate type of finance how to use the book's business plan document template to write your own plan In addition to containing everything you need to know to prepare and write a convincing and sound business plan and then put it into practice, this revised and updated Guide to Business Planning will be invaluable to anyone involved in any form of strategic analysis or business plannings